Application of Overall Equipment Effectiveness In Increasing Productivity: Case Of Textile Company - Muhammad Ahmed Kalwar; Asif Nawaz Wassan; Muhammad Ali Khan; Muzamil Hussain Wadho; Shakeel Ahmed Shaikh; Bahawal Ali Memon (WPOM : Working Papers on Operations Management)
Overall equipment effectiveness (OEE) is a lean manufacturing tool that has been reported to improve the performance of a company significantly. The adoption of OEE has been mattering in the garment manufacturing sector in Pakistan. Numerous companies have implemented OEE and improved their production in the textile sector. The present research was conducted at ABC Textile Company in Karachi. Targets at the various departments of the company were not being achieved. In this regard, the production data for the previous 90 days was collected initially. Since there were the issues with availability of materials and accessories; this was the basic and main reason for delays and unachievable targets. After certain improvements, the overall equipment effectiveness (OEE) of each department was calculated. Data analysis was conducted in Microsoft Excel. Results indicated a significant increase in the value of OEE across all the departments after the process improvement. Since there is a separate tool to increase the availability (total productive maintenance), and quality (Six Sigma); they are implemented one by one. After their integrated implementation, the boost in various parameters of productivity will be noteworthy.